Sejarah Transmisi Keilmuan ke dalam Bahasa Arab - Lailia Nuril Ilma; Muhammad Numan (LPPM Institut Agama Islam Nahdlatul Ulama Kebumen, 2023)
Arabic translation in Islamic history played an important role in connecting the civilization of the Arab world with ancient knowledge and foreign cultures. From the time of the Prophet Muhammad to the time of the Ottoman Empire, the translation of science and philosophy was key in the development of science in the Islamic world. During the time of the Prophet Muhammad, the importance of mastering foreign languages and communication with non-Arab communities encouraged translation activities. The Prophet Muhammad himself sent letters to foreign kings and even translated the Koran. During the Umayyad era, the translation of Greek knowledge into Arabic began as a personal initiative of clerics. Furthermore, the Abbasid Daula, especially during the time of Caliph al-Ma'mun, witnessed a large-scale translation movement and the establishment of Bayt al-Hikmah as a translation center. During the Ottoman Empire, Islamic education initially experienced a setback, but Sultan Mahmud II reconstructed the education system, including the curriculum and teaching methods. This article emphasizes that individual hard work and political support in the scientific translation movement were important factors in the development of Islamic civilization. Further research can explore the role of translation in the context of Islamic education and the development of Islamic society today.